PARADIGMA ADMINISTRASI DALAM PENGELOLAAN SEKOLAH - Patsun (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2015)
The changing of vision and paradigm in management of education today widely implicated in the administration and bureaucratic management of education toward service by promoting participation, transparency and accountability. These three elements are expected to boost the quality of education.